REGULATION OF FOREIGN INVESTMENTS IN THE DEVELOPMENT OF NEW RENEWABLE ENERGY (EBT) IN INDONESIA - Haryanto, Imam (Faculty of Law, Pembangunan Nasional Veteran Jakarta University, 2020)
In the use of energy in Indonesia, is still completely dependent on non-renewable energy such as petroleum, coal and natural gas as the source of its energy needs. After being implemented by the government to realize the renewable energy mix it still experiences various obstacles including technical, non-technical and price competition with fossil energy which tends to be cheaper, causing development of renewable energy is hampered and the energy mix achieved is only around 6.2% overall with growth of 0.39 per year. This research will discuss the effectiveness of regulations issued by the Indonesian government relating to foreign investment in the renewable energy sector. The purpose of this research, will contribute in the form of ideas to relevant agencies, such as the Ministry of Energy and Mineral Resources of the Republic of Indonesia because it is directly related to renewable energy in Indonesia. The method that will be used in this research is empirical normative juridical, which uses facts in the field and is analyzed based on applicable laws and regulations.Keywords: Renewable Energy, Investment, Foreign